1999
DOI: 10.1164/ajrccm.160.1.9806146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerosolized Uridine-5 ′ -Triphosphate on Airway Clearance with Cough in Patients with Primary Ciliary Dyskinesia

Abstract: Primary ciliary dyskinesia (PCD) is a genetic disease characterized by abnormal ciliary structure and function and impaired mucociliary clearance. Because patients with PCD use cough clearance as an airway defense mechanism, we tested the hypothesis that aerosolized uridine-5'-triphosphate (UTP) would improve clearance during cough by its actions to stimulate Cl- secretion and mucin release by goblet cells. We measured clearance during cough in 12 patients with PCD (ages 14 to 71 yr, FEV1 43% to 89% predicted)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 26 publications
0
51
0
1
Order By: Relevance
“…Our findings that other purinergic or ␤-adrenergic agonists also failed to increase CBF in small airways is consistent with this hypothesis. By contrast, increases in airway mucoclearance in response to purinergic agonists or UTP in patients with primary ciliary dyskinesia have been reported (33). However, in view of the inherent ciliary dysfunction, it is likely that these increases in mucus transport result from changes of other components of the mucociliary interface rather than being the result of a direct effect on the cilia.…”
Section: Discussionmentioning
confidence: 94%
“…Our findings that other purinergic or ␤-adrenergic agonists also failed to increase CBF in small airways is consistent with this hypothesis. By contrast, increases in airway mucoclearance in response to purinergic agonists or UTP in patients with primary ciliary dyskinesia have been reported (33). However, in view of the inherent ciliary dysfunction, it is likely that these increases in mucus transport result from changes of other components of the mucociliary interface rather than being the result of a direct effect on the cilia.…”
Section: Discussionmentioning
confidence: 94%
“…Physiologic data have shown that "effective" coughs may result in lung clearance almost equal to normal mucociliary clearance over short time periods, even in subjects with PCD who lack clearance at baseline (24). Chronic airway infection and inflammation lead to bronchiectasis in almost all patients by early adulthood, and pulmonary function testing typically shows progressive, airflow-obstructive defects.…”
Section: Original Researchmentioning
confidence: 99%
“…The higher Ca 2ϩ i mobilization may be particularly useful to CF patients, who depend solely on CaCC to compensate for the absent cAMP-mediated Cl Ϫ secretion in CF (3). Thus, the approximate doubling of Ca and ciliary beat to transiently restore mucus clearance (28).…”
Section: Er Ca 2ϩ Stores In Cf Airway Epitheliamentioning
confidence: 99%